Chinese tourists in Iceland: Motivation and satisfaction - Yingying Xing 1989- (2020)
International tourism has been developing rapidly and China has become a leading force in generating outbound tourists. It has become a trend for more people from China to travel abroad on their own instead of participating in packaged tours. In recent years, Iceland has gained increasing popularity among Chinese tourists, but research has shown that their satisfaction is lower compared to tourists from other nationalities. This thesis introduces a research conducted among Chinese tourists in Iceland with the aim of better understanding their travel motivation and trip satisfaction. Data was collected through semi-structured interviews with 17 independent travellers from China after their trip in Iceland. The findings reveal a variety of motivations shared by the interviewees which can be grouped into four categories: escaping daily life and searching for novelty, Icelandic nature, Icelandic culture and safety. All of the four categories of motivations impacted the interviewees’ decision to travel to Iceland. At the same time, these motivations influenced their trip experience, sometimes positively but sometimes negatively. In addition to their the motivations, their personal preference and past travel experiences also impacted whether or not they appreciated certain trip experiences. Together these factors shaped their trip satisfaction. Despite disliking certain experiences, the interviewees were generally very satisfied towards their trip to Iceland. Ferðamennska hefur vaxið mjög á heimsvísu og kemur stór hluti alþjóðlegra ferðamanna frá Kína. Kínverjar ferðast til útlanda í auknum mæli á eigin vegum í stað hópferða. Á undanförnum árum hefur Ísland notið mikilla vinsælda meðal kínverskra ferðamanna. Rannsóknir hafa þó sýnt að ánægja þeirra er minni en annarra þjóða sem koma til Íslands. Ritgerð þessi fjallar um rannsókn sem var gerð meðal kínverskra ferðamanna á Íslandi. Markmið hennar var að varpa ljósi á þá hvata sem liggja að baki ferðalaga þeirra og hvað mótaði ánægju þeirra. Tekin voru hálfstöðluð ...